2017
DOI: 10.1519/jsc.0000000000001463
|View full text |Cite
|
Sign up to set email alerts
|

Walking Exercise Simultaneously Combined With Neuromuscular Electrical Stimulation of Antagonists Resistance Improved Muscle Strength, Physical Function, and Knee Pain in Symptomatic Knee Osteoarthritis: A Single-Arm Study

Abstract: Matsuse, H, Hashida, R, Takano, Y, Omoto, M, Nago, T, Bekki, M, and Shiba, N. Walking exercise simultaneously combined with neuromuscular electrical stimulation of antagonists resistance improved muscle strength, physical function, and knee pain in symptomatic knee osteoarthritis: a single-arm study. J Strength Cond Res 31(1): 171-180, 2017-A hybrid training system (HTS) was developed as a way to combine the application of electrical stimulation and voluntary contraction. Moreover, we developed a novel trainin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…Besides physical exercise, electric and electromagnetic stimulation has been used for muscle training . Electromagnetic stimulation appears to dominate over the electrical stimulation as it induces double the peak torque, penetrates deeper into the tissue and is not associated with any pain or risks of burns .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides physical exercise, electric and electromagnetic stimulation has been used for muscle training . Electromagnetic stimulation appears to dominate over the electrical stimulation as it induces double the peak torque, penetrates deeper into the tissue and is not associated with any pain or risks of burns .…”
Section: Introductionmentioning
confidence: 99%
“…Besides physical exercise, electric and electromagnetic stimulation has been used for muscle training. [6][7][8] Electromagnetic stimulation appears to dominate over the electrical stimulation as it induces double the peak torque, 9 penetrates deeper into the tissue 10 and is not associated with any pain 9 or risks of burns. 11,12 As electromagnetic stimulation has been shown to strengthen the muscles, 9,13,14 and an intensive muscle training was shown to induce lipolysis, 15,16 we hypothesize that the concept of electromagnetic stimulation can be The treatment was applied in a supine position with the device applicator positioned over the umbilicus.…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, FES has been utilized predominantly to promote lower and upper extremity functions [11,12,16,[20][21][22][23][24] and to a lesser extent to activate the abdominal and torso muscles [8,25,26]. For many years, FES systems included a battery-powered stimulator connected with lead wires to the stimulating electrodes and a wired external trigger to synchronize muscle contraction with the functional activity [27,28].…”
Section: Fes As a Clinical Training Toolmentioning
confidence: 99%
“…Other studies demonstrated that electrically induced contractions signi icantly increase total RNA content and reduce protein degradation [8], increase body cell mass, attenuate reduction of intracellular water, alleviate arterial hemodynamic disturbance [9], reduce tumor necrosis factor (TNFalpha) that is associated with systemic in lammation, and increase beta-endorphin levels [10]. The enhancement of these molecular and cellular metabolic events are all markers supporting long-established clinical data demonstrating that using FES is likely to result in signi icant muscle strength gains whether the strength de icits were a result of damage to the musculoskeletal, neurological or cardiovascular-pulmonary systems [11][12][13][14][15]. Moreover, FES activation of skeletal muscles has been shown to enhance arterial, venous and lymphatic low [16][17][18][19], while concurrently transmitting multimodal afferent signals to multiple sites within the brain's regions of interest (ROI) [1][2][3][4].…”
mentioning
confidence: 96%
“…NSAIDs may not provide sufficient relief from joint pain, they often induce gastrointestinal discomfort, and can adversely interact with other drugs (2). Physical therapy and other alternative medical interventions are effective most of time, but the effects are not longlasting (3,4). Surgical interventions with arthroscopic lavage and debridement may be offered for refractory joint pain when medical therapies fail, but the benefits of these procedures are debated (5).…”
mentioning
confidence: 99%